Fireproof aviation cable line coating composite material and preparation method thereof
By using modified attapulgite and zirconium phosphate composite powder and modified nano-zinc oxide dispersion in cable covering materials, the problem of poor aging resistance of existing cable covering materials is solved and higher flame retardant properties are achieved. and mechanical strength, extending the service life of cable lines.
Patent Information
- Application Number
- CN202411458870.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cable coating materials have poor aging resistance and are prone to reduce their service life due to temperature and other factors during long-term use.
Use a refractory aviation cable line to cover the composite material, including high -density polyethylene, modified bumpbone and phosphate composite powder and modified nano -zinc oxide dispersing liquid. , Enhance the flame retardant performance and mechanical strength of the material.
This material enhances the stretching performance and flame retardant performance through the addition of composite powder. The uniform dispersing of the modified nano -zinc oxide has improved the mechanical strength and aging resistance performance, and extended the life of the cable line.
Smart Images

Figure CN119331337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable coating materials, in particular to a fire-resistant aviation cable line coating composite material and a preparation method thereof. Background Art
[0002] The Chinese patent with publication number CN106317601A discloses a cross-linked flame-retardant cable coating material, comprising: 40-100 parts by weight of a cross-linked base resin, 80-140 parts by weight of a hydrated metal hydroxide flame retardant, 1-5 parts by weight of a peroxide cross-linking agent, and 0.1-0.7 parts by weight of an antioxidant, wherein the antioxidant comprises a polyhedral hindered phenol type antioxidant; the cross-linked flame-retardant cable coating material of the invention has excellent flame retardancy and mechanical properties. However, the cable coating material prepared by the above-mentioned prior art solution has poor aging resistance, so during long-term use, it is easily affected by factors such as temperature to reduce its service life; for this reason, the present invention provides a fire-resistant aviation cable line coating composite material and a preparation method to solve the above-mentioned technical problems. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a fire-resistant aviation cable line coating composite material and a preparation method thereof, which solves the problems mentioned in the above background technology.
[0004] To achieve the above objectives, the present invention is implemented by the following technical solutions: A fire-resistant aviation cable line coating composite material, comprising the following components in parts by weight: 20 to 35 parts of high-density polyethylene, 1.6 to 2.5 parts of flame-retardant filler, and 0.3 to 0.5 parts of a modification aid;
[0005] The flame retardant filler is a composite powder of modified attapulgite and zirconium phosphate, and the mass ratio of the modified attapulgite to zirconium phosphate is 1:(0.6-0.8), and the modification auxiliary agent is a modified nano zinc oxide dispersion.
[0006] Preferably, the preparation method of the modified attapulgite is:
[0007] S1. treating the attapulgite with acid;
[0008] S2, pour the treated attapulgite into 280-300 mL of anhydrous ethanol, stir and ultrasonically disperse for 50-60 min to obtain solution 1;
[0009] S3, pour Co(NO3)2·6H2O and 0.002 mol of hydrochloric acid into 90-100 mL of anhydrous ethanol, stir until completely dissolved, and obtain solution 2;
[0010] S4, mixing solution 1 and solution 2, and performing ultrasonic dispersion treatment for 80 to 100 minutes;
[0011] S5. Pour 2-methylimidazole into 200-210 mL of anhydrous ethanol and stir until completely dissolved to obtain solution 3;
[0012] S6, pour solution 3 into the mixed solution of S4, and treat with ultrasound at room temperature for 4-5h;
[0013] S6. The reaction product is washed with anhydrous ethanol and distilled water in turn, and then placed in a drying oven at 60° C. for 10 to 12 hours, and finally ground to obtain a modified attapulgite.
[0014] Preferably, the weight proportions of the components added in the modified attapulgite are: 7 to 10 parts of acid-treated attapulgite, 5.5 to 8 parts of Co(NO3)2·6H2O, and 15.8 to 17.2 parts of 2-methylimidazole.
[0015] Preferably, the specific processing method in S1 is:
[0016] S11, pour 8-10 g of attapulgite into 1 L of 8 mol / L concentrated hydrochloric acid solution, heat to 65-70° C., and stir for 10-12 h;
[0017] S12, wash with distilled water 4 to 6 times until it is neutral;
[0018] S13, filter and collect the acid-treated product, dry it in a drying oven at 60-65°C for 10-12 hours, and then grind it.
[0019] Preferably, the preparation method of the modified nano zinc oxide dispersion is:
[0020] ①Preparation of nano zinc oxide dispersion;
[0021] ② Pour the nano zinc oxide dispersion into the chloroprene rubber latex under stirring and mix well;
[0022] ③ Pour into 50-60 mL of calcium chloride solution and stir evenly to obtain modified nano zinc oxide.
[0023] Preferably, the weight fractions of the components added in the modified nano zinc oxide dispersion are: 10-13 parts of nano zinc oxide dispersion, 25-30 parts of chloroprene rubber latex; and the mass fraction of the calcium chloride solution is 10%.
[0024] Preferably, in said ①, the specific preparation method of the nano zinc oxide dispersion is:
[0025] Ⅰ. Pour 10-12g of polymer dispersant into deionized water to dissolve;
[0026] Ⅱ. Raise the temperature to 50-55℃, add 15-20g of zinc oxide powder while stirring, and continue stirring at this temperature for 8-10 minutes;
[0027] Ⅲ. Pour into the emulsifier and emulsify at a speed of 1800-2000 rad / min for 40-50 minutes;
[0028] IV. After ultrasonic treatment for 25 to 35 minutes, adjust the pH of the solution to 9.5 to 10;
[0029] V. Pour into a high-speed and high-pressure nano-disperser and process for 8 to 15 minutes to obtain a nano zinc oxide dispersion.
[0030] Preferably, the dispersant is YL-5040.
[0031] A method for preparing a fire-resistant aviation cable line coating composite material comprises the following preparation steps:
[0032] Step 1, weigh each raw material;
[0033] Step 2: Evenly mix the hot-air dried elastomer, flame retardant filler and modified additive, and dry them at 95-100° C. for 2-6 hours in a dehumidifying dryer to obtain a fire-resistant aviation cable line coating composite material.
[0034] Beneficial Effects
[0035] The present invention provides a fire-resistant aviation cable line coating composite material and a preparation method thereof. Compared with the prior art, it has the following beneficial effects:
[0036] (1) The fire-resistant aviation cable line coating composite material and preparation method thereof, by combining attapulgite and zirconium phosphate as a flame retardant, the addition of the composite powder can fill the gaps in the matrix material, thereby enhancing the tensile properties of the composite material. At the same time, the addition of the composite powder makes the carbon layer more dense and continuous, thereby effectively isolating the heat exchange between the material and the outside world, and improving the flame retardant properties of the composite material; by modifying the attapulgite, the dispersibility of the attapulgite is improved, so that it can be evenly dispersed in the zirconium phosphate, so that the zirconium phosphate can be evenly grafted on each attapulgite, thereby improving the synergistic effect of the composite powder.
[0037] (2) The fire-resistant aviation cable line coating composite material and preparation method modify the nano zinc oxide dispersion so that the latex wraps the nano zinc oxide, effectively preventing the nano zinc oxide from agglomerating, and improving the dispersion effect of the nano zinc oxide in the composite material. The nano zinc oxide can be evenly dispersed in the matrix at the nanoscale, thereby improving the affinity with the matrix, thereby improving the mechanical strength and aging resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Projection electron microscope images of the attapulgite provided by the present invention before and after modification;
[0039] Figure 2 These are SEM images of the nano zinc oxide dispersion provided by the present invention before and after modification. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A method for preparing a fire-resistant aviation cable line coating composite material comprises the following preparation steps:
[0043] Step 1, weigh the raw materials: 40 g of ethylene-vinyl acetate copolymer, 2.5 g of modified attapulgite and zirconium phosphate composite powder with a mass ratio of 1:0.6, and 0.5 g of modified nano zinc oxide dispersion;
[0044] The preparation method of the modified attapulgite is as follows: pour 8g of attapulgite into 1L of concentrated hydrochloric acid solution with a concentration of 8mol / L, heat to 65°C, and stir for 10h; wash with distilled water 4 times until it is neutral; filter and collect the acid-treated product, place it in a drying oven at 60°C for 10h, and then crush it to obtain the acid-treated attapulgite; take 7g of the treated attapulgite and pour it into 280mL of anhydrous ethanol, stir and ultrasonically disperse it for 50min to obtain solution 1; add 5.5g of Co(NO3)2·6H2O and 0.0 0.2 mol of hydrochloric acid was poured into 90 mL of anhydrous ethanol, stirred until completely dissolved, and solution 2 was obtained; solution 1 was mixed with solution 2, and ultrasonic dispersion treatment was performed for 80 min; 15.8 g of 2-methylimidazole was poured into 200 mL of anhydrous ethanol, stirred until completely dissolved, and solution 3 was obtained; solution 3 was poured into the mixture of solution 1 and solution 2, and ultrasonic treatment was performed for 4 h at room temperature; the reaction product was rinsed with anhydrous ethanol and distilled water in turn, and then placed in a drying oven at 60 ° C for 10 h, and finally ground to obtain modified attapulgite;
[0045] The preparation method of the modified nano zinc oxide dispersion is as follows: pour 10g of YL-5040 into deionized water for dissolution; heat to 50°C, add 15g of zinc oxide powder while stirring, and continue stirring at this temperature for 8min; pour into an emulsifier, emulsify at a speed of 1800rad / min for 40min; after ultrasonic treatment for 25min, adjust the pH of the solution to 9.5; pour into a high-speed high-pressure nanodisperser for treatment for 8min to obtain a nano zinc oxide dispersion; under stirring conditions, pour 10g of the nano zinc oxide dispersion into 25g of chloroprene rubber latex and mix well; pour into 50mL of calcium chloride solution and stir well to obtain the modified nano zinc oxide;
[0046] Step 2: Evenly mix the hot-air dried elastomer, flame retardant filler and modified additive, and dry them at 95° C. for 2 hours in a dehumidifying dryer to obtain a fire-resistant aviation cable line coating composite material.
[0047] Example 2
[0048] A method for preparing a fire-resistant aviation cable line coating composite material comprises the following preparation steps:
[0049] Step 1, weigh the raw materials: 50g of polyvinyl chloride, 2g of modified attapulgite and zirconium phosphate composite powder with a mass ratio of 1:0.7, and 0.4g of modified nano zinc oxide dispersion;
[0050] The preparation method of the modified attapulgite is as follows: 9 g of attapulgite is poured into 1 L of concentrated hydrochloric acid solution with a concentration of 8 mol / L, heated to 68°C, and stirred for 11 hours; washed with distilled water for 5 times until it is neutral; filtered to collect the acid-treated product, and then dried in a drying oven at 63°C for 11 hours and then crushed to obtain the acid-treated attapulgite; 8.5 g of the treated attapulgite is poured into 290 mL of anhydrous ethanol, stirred and ultrasonically dispersed for 55 minutes to obtain solution 1; 6.5 g of Co(NO3)2·6H2O and 0. 002mol of hydrochloric acid was poured into 95mL of anhydrous ethanol, stirred until completely dissolved, and solution 2 was obtained; solution 1 was mixed with solution 2, and ultrasonic dispersion treatment was performed for 90min; 16.5g of 2-methylimidazole was poured into 205mL of anhydrous ethanol, stirred until completely dissolved, and solution 3 was obtained; solution 3 was poured into the mixture of solution 1 and solution 2, and ultrasonic treatment was performed for 5h at room temperature; the reaction product was rinsed with anhydrous ethanol and distilled water in turn, and then placed in a drying oven at 60°C for 11h, and finally ground to obtain modified attapulgite;
[0051] The preparation method of the modified nano zinc oxide dispersion is as follows: 11 g of YL-5040 is poured into deionized water for dissolution; the temperature is raised to 55° C., 18 g of zinc oxide powder is added while stirring, and stirring is continued at the temperature for 9 minutes; the solution is poured into an emulsifier and emulsified at a speed of 1900 rad / min for 45 minutes; after ultrasonic treatment for 30 minutes, the pH value of the solution is adjusted to 9.8; the solution is poured into a high-speed high-pressure nanodispersor for treatment for 10 minutes to obtain a nano zinc oxide dispersion; under stirring conditions, 12 g of the nano zinc oxide dispersion is poured into 28 g of chloroprene rubber latex and mixed; the solution is poured into 55 mL of calcium chloride solution and stirred evenly to obtain the modified nano zinc oxide;
[0052] Step 2: Evenly mix the hot-air dried elastomer, flame retardant filler and modified additive, and dry them at 98° C. for 4 hours in a dehumidifying dryer to obtain a fire-resistant aviation cable line coating composite material.
[0053] Example 3
[0054] A method for preparing a fire-resistant aviation cable line coating composite material comprises the following preparation steps:
[0055] Step 1, weigh the raw materials: 60 g of hydrogenated styrene-butadiene block copolymer, 1.6 g of modified attapulgite and zirconium phosphate composite powder with a mass ratio of 1:0.8, and 0.3 g of modified nano zinc oxide dispersion;
[0056] The preparation method of the modified attapulgite is as follows: pour 10g of attapulgite into 1L of concentrated hydrochloric acid solution with a concentration of 8mol / L, heat to 70°C, and stir for 12h; wash with distilled water 6 times until it is neutral; filter and collect the acid-treated product, place it in a drying oven at 65°C for 12h, and then crush it to obtain the acid-treated attapulgite; take 10g of the treated attapulgite and pour it into 300mL of anhydrous ethanol, stir and ultrasonically disperse it for 60min to obtain solution 1; add 8g of Co(NO3)2·6H2O and 0.00 2 mol of hydrochloric acid was poured into 100 mL of anhydrous ethanol, stirred until completely dissolved, and solution 2 was obtained; solution 1 was mixed with solution 2, and ultrasonic dispersion treatment was performed for 100 min; 17.2 g of 2-methylimidazole was poured into 210 mL of anhydrous ethanol, stirred until completely dissolved, and solution 3 was obtained; solution 3 was poured into the mixture of solution 1 and solution 2, and ultrasonic treatment was performed for 5 h at room temperature; the reaction product was rinsed with anhydrous ethanol and distilled water in turn, and then placed in a drying oven at 60°C for 12 h, and finally ground to obtain modified attapulgite;
[0057] The preparation method of the modified nano zinc oxide dispersion is as follows: 12g of YL-5040 is poured into deionized water for dissolution; the temperature is raised to 55°C, 20g of zinc oxide powder is added while stirring, and stirring is continued for 10min at the temperature; the solution is poured into an emulsifier and emulsified at a speed of 2000rad / min for 50min; after ultrasonic treatment for 35min, the pH value of the solution is adjusted to 10; the solution is poured into a high-speed high-pressure nanodispersor for treatment for 15min to obtain a nano zinc oxide dispersion; under stirring conditions, 13g of the nano zinc oxide dispersion is poured into 30g of chloroprene rubber latex and mixed; the solution is poured into 60mL of calcium chloride solution and stirred evenly to obtain the modified nano zinc oxide;
[0058] Step 2: Evenly mix the hot-air dried elastomer, flame retardant filler and modified additive, and dry them at 100° C. for 6 hours in a dehumidifying dryer to obtain a fire-resistant aviation cable line coating composite material.
[0059] Comparative Example 1
[0060] Compared with Example 1, the flame retardant modified attapulgite and zirconium phosphate composite powder in Example 1 is replaced by attapulgite and zirconium phosphate composite powder.
[0061] Comparative Example 2
[0062] Compared with Example 1, the flame retardant modified attapulgite and zirconium phosphate composite powder in Example 1 is replaced by modified attapulgite.
[0063] Comparative Example 3
[0064] Compared with Example 1, the modified nano zinc oxide dispersion in Example 1 is replaced by the nano zinc oxide dispersion.
[0065] Sample preparation: The composite material was extruded and granulated with a screw, and five temperature control sections were set, the first temperature control section was 160-200°C, the second temperature control section was 170-230°C, the third temperature control section was 180-250°C, the fourth temperature control section was 200-250°C, and the fifth temperature control section was 200-255°C. The screw speed was 55r / min and the main engine speed was 200r / min.
[0066] Aging test: Test in accordance with GB / T2951.12-2008. The specific steps are as follows: Hang the sample in the middle of the air heat aging test chamber. Keep the distance between each sample and any other sample at least 20mm, and do not contact the inner wall of the aging chamber, except for the metal binding wire. Then turn on the heating of the aging chamber, start timing when the temperature rises to 100℃, and take out the sample after 240 hours for subsequent testing.
[0067] Mechanical properties test: tensile strength and elongation at break were tested according to GB / T1040-92, with a tensile rate of 10 mm / min and a sample size of 100 mm×6 mm×1 mm. The results are shown in Table 1.
[0068] Limiting oxygen index: tested in accordance with GB2406-80, the sample size is 120mm×10mm×4mm; the results are shown in Table 1.
[0069] Vertical combustion performance: tested in accordance with GB4609-84, the sample size is 120mm×10mm×4mm; the results are shown in Table 1.
[0070] Table 1
[0071]
[0072] like Figure 1 As shown, the surface of the unmodified attapulgite is relatively smooth and agglomerates, and the rod-like structures are regularly aggregated; while a large number of smaller grains appear on the surface of the modified attapulgite nanorods, and the rods are separated, gaps appear between the rods, and the agglomeration phenomenon between the attapulgite rods is improved.
[0073] like Figure 2 As shown in the figure, before modification, large holes appeared on the surface of the nano zinc oxide dispersion, and the particles showed uneven aggregation distribution in it, with serious agglomeration, and the particle size had deviated from the nanoscale. However, after modification, no large agglomerates appeared in the nano zinc oxide dispersion, most of the nanoparticles were evenly dispersed at the nanoscale, and no holes appeared in the photo, indicating that the system has good compatibility.
[0074] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A fire-resistant aviation cable line coating composite material, characterized in that: The invention comprises the following components in parts by weight: 40 to 60 parts of elastomer, 1.6 to 2.5 parts of flame retardant filler, and 0.3 to 0.5 parts of modification auxiliary agent; Among them, the elastomer is ethylene-vinyl acetate copolymer, polyvinyl chloride or hydrogenated styrene-butadiene block copolymer; the flame retardant filler is a composite powder of modified attapulgite and zirconium phosphate, and the mass ratio of modified attapulgite to zirconium phosphate is 1:(0.6-0.8); the modification auxiliary agent is a modified nano zinc oxide dispersion.
2. The fire-resistant composite material for aviation cable line coating according to claim 1, characterized in that: The preparation method of the modified attapulgite is: S1. treating the attapulgite with acid; S2, pour the treated attapulgite into 280-300 mL of anhydrous ethanol, stir and ultrasonically disperse for 50-60 min to obtain solution 1; S3, pour Co(NO3)2·6H2O and 0.002 mol of hydrochloric acid into 90-100 mL of anhydrous ethanol, stir until completely dissolved, and obtain solution 2; S4, mixing solution 1 and solution 2, and performing ultrasonic dispersion treatment for 80 to 100 minutes; S5. Pour 2-methylimidazole into 200-210 mL of anhydrous ethanol and stir until completely dissolved to obtain solution 3; S6, pour solution 3 into the mixed solution of S4, and treat with ultrasound at room temperature for 4-5h; S6. The reaction product is washed with anhydrous ethanol and distilled water in turn, and then placed in a drying oven at 60° C. for 10 to 12 hours, and finally ground to obtain a modified attapulgite.
3. The fire-resistant composite material for aviation cable line coating according to claim 2, characterized in that: The weight proportions of the components added in the modified attapulgite are: 7-10 parts of acid-treated attapulgite, 5.5-8 parts of Co(NO3)2·6H2O, and 15.8-17.2 parts of 2-methylimidazole.
4. The fire-resistant composite material for aviation cable line coating according to claim 2, characterized in that: The specific processing method in S1 is: S11, pour 8-10 g of attapulgite into 1 L of 8 mol / L concentrated hydrochloric acid solution, heat to 65-70° C., and stir for 10-12 h; S12, wash with distilled water 4 to 6 times until it is neutral; S13, filter and collect the acid-treated product, dry it in a drying oven at 60-65°C for 10-12 hours, and then grind it.
5. The fire-resistant composite material for aviation cable line coating according to claim 1, characterized in that: The preparation method of the modified nano zinc oxide dispersion is: ①Preparation of nano zinc oxide dispersion; ② Pour the nano zinc oxide dispersion into the chloroprene rubber latex under stirring and mix well; ③ Pour into 50-60 mL of calcium chloride solution and stir evenly to obtain modified nano zinc oxide.
6. The fire-resistant composite material for aviation cable line coating according to claim 5, characterized in that: The weight fractions of the components added in the modified nano zinc oxide dispersion are: 10-13 parts of nano zinc oxide dispersion and 25-30 parts of chloroprene rubber latex; the mass fraction of the calcium chloride solution is 10%.
7. The fire-resistant composite material for aviation cable line coating according to claim 5, characterized in that: In the above ①, the specific preparation method of the nano zinc oxide dispersion is: Ⅰ. Pour 10-12g of polymer dispersant into deionized water to dissolve; Ⅱ. Raise the temperature to 50-55℃, add 15-20g of zinc oxide powder while stirring, and continue stirring at this temperature for 8-10 minutes; Ⅲ. Pour into the emulsifier and emulsify at a speed of 1800-2000 rad / min for 40-50 minutes; IV. After ultrasonic treatment for 25 to 35 minutes, adjust the pH of the solution to 9.5 to 10; V. Pour into a high-speed and high-pressure nano-disperser and process for 8 to 15 minutes to obtain a nano zinc oxide dispersion.
8. The fire-resistant composite material for aviation cable line coating according to claim 7, characterized in that: The dispersant is YL-5040.
9. A method for preparing the fire-resistant aviation cable line coating composite material according to claim 8, characterized in that: The method comprises the following preparation steps: Step 1, weigh each raw material; Step 2: Evenly mix the hot-air dried elastomer, flame retardant filler and modified additive, and dry them at 95-100° C. for 2-6 hours in a dehumidifying dryer to obtain a fire-resistant aviation cable line coating composite material.
Citation Information
Patent Citations
Cross-linking and flame-retardant cable cladding material
CN106317601A
Nano zinc oxide / rubber composite material and preparation method thereof
CN109749168A
Special light flame-retardant insulating coiled material for cable line coating as well as preparation method and application of special light flame-retardant insulating coiled material
CN115386157A
Flexible fireproof robot cable
CN115960424A
Environment-friendly flame-retardant smoke-suppression antistatic filler for waterborne epoxy resin coating and preparation method thereof
CN116200063A